The effectiveness of hyperoxygenation in preventing oxygen desaturation in intubated infants treated with endotracheal suctioning - Sholihatul Amaliya; Yeni Rustina; Defi Efendi (Healthcare in Low-resource Settings, 2024)
Endotracheal suctioning is an effective nursing intervention for intubated infants undergoing invasive mechanical ventilation. However, this intervention has the potential to cause side effects, such as hypoxemia, which typically requires hyperoxygenation. Despite the widespread use of hyperoxygenation in clinical practice, there are limited reports on its effectiveness in infants. This study aims to determine the effect of hyperoxygenation on oxygen saturation of intubated infants. The study procedures were carried out using a quasi-experimental method with a cross-over approach. In addition, the sample population comprised 22 intubated infants who were treated at the perinatology unit of Dr. Cipto Mangunkusumo Hospital in Jakarta from March to April 2018. The participants were then divided into 2 groups based on their condition, and oxygen saturation level was assessed. The intervention comprised endotracheal suctioning with and without hyperoxygenation, with a 3-hour washing period. Data collection was performed at different measurement intervals, namely before, during, and after suctioning, followed by statistical analysis. The paired-sample t-tests and Wilcoxon test showed that there was a significant difference in oxygen saturation at certain measurement intervals (p=0.006; p=0.010; p=0.001; p=0.001; p=0.001). In addition, Friedman test also showed the presence of a significant difference in the reduction of oxygen saturation between the control and intervention groups (p=0.001). In conclusion, hyperoxygenation had the potential to prevent the reduction of oxygen saturation during endotracheal suctioning in intubated infants. However, individual assessment of the need for suctioning and hyperoxygenation was necessary for a safe and effective procedure.